Household income, fetal size and birth weight: an analysis of eight populations. Issue 7 (12th April 2022) - Turner, Steve; Posthumus, Anke G; Steegers, Eric A P; AlMakoshi, Amel; Sallout, Bahauddin; Rifas-Shiman, Sheryl L; Oken, Emily; Kumwenda, Ben; Alostad, Fatemah; Wright-Corker, Catherine; Watson, Laura; Mak, Diane; et al.
Abstract : Background: The age at onset of the association between poverty and poor health is not understood. Our hypothesis was that individuals from highest household income (HI), compared to those with lowest HI, will have increased fetal size in the second and third trimester and birth. Methods: Second and third trimester fetal ultrasound measurements and birth measurements were obtained from eight cohorts. Results were analysed in cross-sectional two-stage individual patient data (IPD) analyses and also a longitudinal one-stage IPD analysis. Results: The eight cohorts included 21 714 individuals. In the two-stage (cross-sectional) IPD analysis, individuals from the highest HI category compared with those from the lowest HI category had larger head size at birth (mean difference 0.22 z score (0.07, 0.36)), in the third trimester (0.25 (0.16, 0.33)) and second trimester (0.11 (0.02, 0.19)). Weight was higher at birth in the highest HI category. In the one-stage (longitudinal) IPD analysis which included data from six cohorts (n=11 062), head size was larger (mean difference 0.13 (0.03, 0.23)) for individuals in the highest HI compared with lowest category, and this difference became greater between the second trimester and birth. Similarly, in the one-stage IPD, weight was heavier in second highest HI category compared with the lowest (mean difference 0.10 (0 .00, 0.20)) and the difference widened as pregnancy progressed. Length was not linked to HI category in the longitudinal model. Conclusions: The association between HI, an index of poverty, and fetal size is already present in the second trimester.